Systematic and dynamic pedagogical discourse of José María Arguedas under Peruvian education - Callalli Pimentel, Aldo (2014)
This essay addresses the main theses that comprise pedagogical discourse of José María Arguedas and its direct influence on the historical process of Peruvian education. It will analyze program structure Arguedian systemic dynamics in the areas of political, economic, social and cultural, as a correlate of the changes and transformations in our country, aiming to weave theoretical support necessary for the understanding of the teaching-learning processes in the context ofglobalization.